Role and mechanism of fibroblast-activated protein-α expression on the surface of fibroblast-like synoviocytes in rheumatoid arthritis - Wang, Zihan; Wang, Jinping; Lan, Tianyi; Zhang, Liubo; Yan, Zeran; Zhang, Nan; Xu, Yuan; Tao, Qingwen (Frontiers in Immunology, 2023)
Fibroblast-activated protein-α (FAP) is a type II integrated serine protease expressed by activated fibroblasts during fibrosis or inflammation. Fibroblast-like synoviocytes (FLSs) in rheumatoid arthritis (RA) synovial sites abundantly and stably overexpress FAP and play important roles in regulating the cellular immune, inflammatory, invasion, migration, proliferation, and angiogenesis responses in the synovial region. Overexpression of FAP is regulated by the initial inflammatory microenvironment of the disease and epigenetic signaling, which promotes RA development by regulating FLSs or affecting the signaling cross-linking FLSs with other cells at the local synovium and inflammatory stimulation. At present, several treatment options targeting FAP are in the process of development. This review discusses the basic features of FAP expressed on the surface of FLSs and its role in RA pathophysiology and advances in targeted therapies.